Approaches for estimating benefits and costs of interventions in plant biosecurity across invasion phases - Welsh, Melissa J; Turner, James A; Epanchin-Niell, Rebecca S; Monge, Juan J; Soliman, Tarek; Robinson, Andrew P; Kean, John M; Phillips, Craig; Stringer, Lloyd D; Vereijssen, Jessica; Liebhold, Andrew M; Kompas, Tom; et al. (Ecological applications, 2021)
Nonnative plant pests cause billions of dollars in damages. It is critical to prevent or reduce these losses by intervening at various stages of the invasion process, including pathway risk management (to prevent pest arrival), surveillance and eradication (to counter establishment), and management of established pests (to limit damages). Quantifying benefits and costs of these interventions is important to justify and prioritize investments and to inform biosecurity policy. However, approaches for these estimations differ in (1) the assumed relationship between supply, demand, and prices, and (2) the ability to assess different types of direct and indirect costs at invasion stages, for a given arrival or establishment probability. Here we review economic approaches available to estimate benefits and costs of biosecurity interventions to inform the appropriate selection of approaches. In doing so, we complement previous studies and reviews on estimates of damages from invasive species by considering the influence of economic and methodological assumptions. Cost accounting is suitable for rapid decisions, specific impacts, and simple methodological assumptions but fails to account for feedbacks, such as market adjustments, and may overestimate long-term economic impacts. Partial equilibrium models consider changes in consumer and producer surplus due to pest impacts or interventions and can account for feedbacks in affected sectors but require specialized economic models, comprehensive data sets, and estimates of commodity supply and demand curves. More intensive computable general equilibrium models can account for feedbacks across entire economies, including capital and labor, and linkages among these. The two major considerations in choosing an approach are (1) the goals of the analysis (e.g., consideration of a single pest or intervention with a limited range of impacts vs. multiple interventions, pests or sectors), and (2) the resources available for analysis such as knowledge, budget and time.
Keywords: Cost-Benefit Analysis; phytosanitary measures; pravděpodobnost; Introduced Species; Risk Management; benefit-cost analysis; border biosecurity; general equilibrium modeling; partial equilibrium modeling; invasive alien species; cost accounting; Probability; řízení rizik; ekonomické modely; analýza nákladů a výnosů; Models, Economic; zavlečené druhy